PENINGKATAN KEMAMPUAN KEUANGAN UMKM DENGAN APLIKASI SMART DIGITAL - Dwianika, Agustine; El Rayeb, Augury; Fitriyah Nurhidayah (FKIP UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
This Community Service Activity (PkM) aims to provide solutions for Small and Medium Enterprises in: 1). Knowledge of financial management, 2). Overall financial management skills, 3). Facilities and infrastructure to support business management in general. In order to support community empowerment programs, in SMEs. The PkM team utilizes research activities in terms of the use of technology in financial management, assistance, infographics, videos, and training to encourage knowledge and skills in partner SME financial management. The results of this community service reported that the partners' knowledge of financial literacy has increased, and financial management skills with the SMART DIGITAL application have also increased. Partners admit that it is easy to use this application and in general, can accommodate their bookkeeping needs easily and inexpensively.